University admission selection for SPM leavers using Rule-Based Expert System / Intan Syazlinda Mohd Shahidon - Mohd Shahidon, Intan Syazlinda (2006)
Entering higher educational institutions such as university is always being one's aim after the Malaysia Certification Examination. They will choose universities and programs they hke, sometimes without taking into consideration the university and program requirements. The problems come to the universities where they need to choose and selects qualified apphcants among thousand of applications. This processes become harder when applicants do not consider the requirements. A system is needed to assist the administrators in selecting the qualified students. Consequently, the processes will be more systematic, efficient and reliable. University Admission Selection For SPM Leavers Using Rule-Based Expert System is an alternatives solution to the problems using Artificial Intelligence approach. This system can help processing the application and then produce output which is tiie list of qualified students for each program as a solution to the problem stated. A rule-based technique is chosen because Ae knowledge in this problem domain can be directly transformed into rules